Membangun Self-Confidence Siswa melalui Pembelajaran Matematika - Andayani, Meri; Amir, Zubaidah (Universitas Islam Negeri Raden Intan Lampung, 2019)
Self-confidence is an important aspect of personality in a person. Self confidence is an attitude or feeling of confidence in one's own abilities so that the person concerned is not too anxious in his actions, can feel free to do things he likes, and is responsible for his actions, warm and polite in interacting with others, have an urge to excel and recognize their strengths and weaknesses. Mathematics learning is one of learning that can generate students' self confidence attitudes, so that it can improve achievement and learning outcomes in school.